Development of a prototype roundlet dough shaper form machine / Muhammad Zakuan Mohd Zulkifli - Mohd Zulkifli, Muhammad Zakuan (2023)
Food is one of the biggest industries in our country including the dough maker. As we know, for the machine at the factory is very big size and expensive. So, it will be burden for the person who work as small entrepreneur. The other problem for the dough maker industry is hard to make a circular form for the dough before it can be a cake. So, my solution to solve these two problems are making a machine that can be afforded to buy and can make the circular shape dough efficiently. If these problems can be solved, it can increase the productivity for the small entrepreneur. My objective for this machine can produce the circular shape dough uniformly within the short time. This machine can also facilitate the small or medium entrepreneur to expand their business in food industry. This machine is to help small entrepreneur for their business